Metacognitive Identification in Solving Mathematics Problems of Junior High School Students - Budi Murtiyasa; Oryza Riana Anggraini (STAI Hubbulwathan Duri, 2022)
This study aims to identify the metacognitive level of students in solving mathematical problems. This research is a descriptive research with a qualitative approach. The subjects in this study were students of class VII a total of 65 students. Data collection techniques in the form of tests and documentation. The data analysis technique is done by reducing the data, presenting the data and drawing conclusions. The results showed that overall students who had high metacognitive abilities were 14%, while students who had moderate metacognitive abilities were 51% and students who had low metacognitive abilities were 35%. Most students with high metacognitive abilities have used their abilities well. While students with moderate metacognitive abilities only a few students who have used their metacognitive abilities. Students with low metacognitive abilities have not used their metacognitive abilities in solving mathematical problems according to the polya stage.